2012
DOI: 10.3892/etm.2012.659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of 18F-FDG PET/CT on initial staging and therapy planning for breast cancer

Abstract: The purpose of this study was to determine the clinical significance of 18F-FDG PET/CT on initial staging and therapy planning in patients with invasive breast cancer. One hundred and forty-one consecutive, biopsy proven preoperative and 195 postoperative high-risk breast cancer patients who were referred for PET/CT for initial staging were included in this retrospective study. The clinical stage had been determined by conventional imaging modalities prior to the PET/CT scan. Of the 141 examined preoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Clinical stage: The rates of DM ranged from 0% to 30%[ 17 - 34 ] for the entire group of reported patients. However, only 9 of the studies correlated DM rates detected by 18 FDG-PET/CT with the clinical stage[ 17 , 22 - 24 , 27 , 29 , 31 , 32 , 34 ]. The rate of DM was lowest among studies of patients with invasive lobular cancer compared to studies that had included a mixture of other histologies, such as invasive ductal carcinoma[ 18 ] (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical stage: The rates of DM ranged from 0% to 30%[ 17 - 34 ] for the entire group of reported patients. However, only 9 of the studies correlated DM rates detected by 18 FDG-PET/CT with the clinical stage[ 17 , 22 - 24 , 27 , 29 , 31 , 32 , 34 ]. The rate of DM was lowest among studies of patients with invasive lobular cancer compared to studies that had included a mixture of other histologies, such as invasive ductal carcinoma[ 18 ] (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the rate of DM for presumed stage I was low for all cancer types but non-negligible, ranging from 0% to 8.3%[ 22 , 27 , 29 , 31 , 32 , 34 ]. Among the 9 studies that reported the rate of DM in patients with stage II breast cancer separately, the prevalence ranged from 0% to 12.4%[ 17 , 22 , 24 , 27 , 29 , 31 , 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In breast cancer, PET-CT has been shown to upstage as many as 58% of preoperative and 32% of postoperative patients, whereas downstaging 2%. 4 Although beyond the scope of this discussion,otherimaginghybridshaveemergedas a result of PET-CT including SPECT-CT and PET-MR.…”
Section: Originsmentioning
confidence: 99%
“…For the initial staging work-up, many conventional imaging modalities, such as X-ray mammography, MR mammography, chest plain radiography, bone scintigraphy, and breast, axillary and liver ultrasonography, have been widely utilized. In recent years, several groups have evaluated the clinical role of FDG-PET/CT for pretreatment evaluation of breast cancer in comparison with conventional imaging tools [18,39,[43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). These studies revealed that FDG-PET/CT is generally helpful, but particularly valuable for detection of extra-axillary (infraclavicular, supraclavicular and internal mammary) nodal metastasis and occult distant metastasis relative to conventional modalities, especially in patients with inflammatory breast cancer [43,46,47] and stage II-III disease [18, Fig.…”
Section: Initial Stagingmentioning
confidence: 99%